Ôkami e mitologia japonesa - associação dos personagens do jogo com elementos da mitologia e do folclore japonês - Anjos, Camila Carvalho dos (Brasil, 2020)
The present work deals about Ōkami - a game available on several video game platforms - and aims to analyze the similarities and differences among its characters and those of mythology, as well as some Japanese folk tales. To do this, was investigated the mythology and folklore of Japan and the way in which game characters are constructed. In addition to the theoretical references on these themes, Krawczyk and Novak (2006) categorization was used, which classify the characters according to the archetypes of characters in video games, together with Joseph Campbell's (2007) monomyth theory, where the hero of myths and tales traces a circular route of departure and returns to his society. Through a comparative analysis among the ten characters selected for the research, the study identified the use of various aspects of mythological narratives, not limited to the evident ones like the proper names of the characters. It was also possible to investigate the use of folkloric narratives, as well as the identification of some original characters of the game - thus classified as there are no characteristic elements strong enough to demonstrate their connection with traditional narratives. Among the distinctions, it was observed that the studio responsible for the game development chose to adapt several aspects that characterize the original narratives to the fruitive reality of the player, aiming at a better gameplay.